Origin of the rotation rates of single white dwarfs and neutron stars - Spruit, H (2001)
I argue that magnetic torques inside stars are likely to maintain a state of approximately uniform rotation on the giant branch. The cores of giants are then very slowly rotating, and the rotation of white dwarfs and neutron stars is not a remnant of the rotation of their main sequence progenitors. The kicks associated with the observed proper motions of pulsars can explain the rotation rates of neutron stars, while slight non-axisymmetries in the mass loss during planetary nebula formation can explain the observed rotation of white dwarfs.